Pemikiran Pendidikan Islam Ibnu Khaldun - Rosyidah, Fahmi; Ummah, Kholifatul; Mabruroh, Nurul; Amrullah, Riyad; Khoir, Mulyanto Abdullah (Lembaga Yasin AlSys, 2026)
Although Ibn Khaldun’s educational thought has been widely discussed in various studies, research that specifically examines its relevance to modern education, particularly in the Indonesian context, remains relatively limited. This study aimed to explore in depth the educational thought of Ibnu Khaldun, describe his intellectual background, and analyze the relevance of his educational concepts to educational practice in the modern era. A qualitative descriptive approach was employed with a library research design and descriptive analysis of Ibnu Khaldun’s works and related literature. The findings show that Ibnu Khaldun’s educational thought has strong relevance to modern Islamic education, including his concept of gradual learning, which aligns with contemporary educational psychology theories; his rejection of coercion and violence, which is consistent with humanistic educational approaches; and his idea of maintaining a balance between religious sciences and rational sciences, which corresponds to the needs of Islamic education in the modern era. These findings affirm that Ibnu Khaldun’s educational thought can serve as an important reference for developing an educational paradigm that is balanced, humanistic, and contextual, while also opening opportunities for further critical exploration of the relevance and application of his ideas in today’s education systems.